Some Suzuki-type best proximity point results on metric spaces endowed a graph - Soomieh Khaleghizadeh (Journal of Hyperstructures)
In this paper, the researcher proved the best proximity point theorem for Suzuki type mappings in the setting of metric spaces endowed a graph. In particular, some earlier results in the literature on both best proximity theory and metric fixed point theory were enriched, extended, and at last generalized.